Improved light extraction of InGaN/GaN blue LEDs by GaOOH NRAs using a thin ATO seed layer - Lee, Hee Kwan (Springer, 2012)
We investigated the effect of gallium oxide hydroxide (GaOOH) nanorod arrays (NRAs) on the light extraction of InGaN/GaN multiple quantum well blue light-emitting diodes (LEDs). GaOOH NRAs were prepared on an indium tin oxide electrode (ITO) layer of LEDs by electrochemical deposition method. The GaOOH NRAs with preferred orientations were grown on the ITO surface by sputtering a thin antimony-doped tin oxide seed layer, which enhances heterogeneous reactions. Surface density and coverage were also efficiently controlled by the different growth voltages. For LEDs with GaOOH NRAs grown at −2 V, the light output power was increased by 22% without suffering from any serious electrical degradation and wavelength shift as compared with conventional LEDs.